ANALISA PENGARUH PEMASANGAN STABILISER TERHADAP KESTABILAN GULING KENDARAAN JALAN 4 RODA - Setiawan, Arif Hari (Jurnal Gamma, 2006)
Critical situation by vehicle of fast moment at turning is vehicle skidding and rolling. Both the things caused by centrifugal force. Vehicle roll to be marked upraisedly its one or two wheel of surface of road. This research is done by measurement of torsion stiffness from one of bar model of stabilizer and its influence to stabilizer rolling stiffness after attached at vehicle. Level of this stabilizer rolling stiffness will be seen its influence to level of angle of rolling vehicle. From result of this research, installation of stabilizer influence at inclination of vehicle body. Angle of rolling vehicle after attached by stabilizer smaller than before attached. This condition caused difference of maximum of turning speed. After attached by stabilizer higger than before attached. Influence of installation of stabilizer to stability of rolling vehicle of this 4 wheel road take its case study at Toyota Kijang LX in road level off with turning radius 50 m. Maximum of turning speed before attached by stabilizer is 64,87 km/hour while after attached become 69,66 km/hour ( increase 7,4 %)